Implementation Strategy of Ship Engine Maintenance Management System to Improve Operational Efficiency - Mursidi, Mursidi; Sarjito, Aris (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2025)
The implementation of a ship machinery maintenance management system is an important aspect to improve operational efficiency and reduce costs. This study aims to analyze the factors that influence the success of the maintenance management system, focusing on training and human resource development. The method used in this research is secondary data analysis, which includes related literature, industry reports, and relevant case studies. The research findings show that top management support, good technical skills, as well as appropriate technology greatly affect the effectiveness of the maintenance system. In addition, planned training and evaluation of training results were shown to improve technician performance, thereby reducing downtime and operational costs. This study concludes that to achieve success in ship machinery maintenance management systems, it is important to invest in human resource development and implement relevant technologies. The practical implications of the findings can serve as a reference for shipping companies to improve their maintenance strategies.